То, из чего растёт счастье: Впечатления жизни - Парфёнова Ольга Владимировна (Удмуртия, 2008)
Экземпляры: ф.19 (20170131) / Инвентарный номер: 52893 / Цена: 50.00 / Авт.знак: П 18 / ГРНТИ: 17.82 / ББК: 84(2Рос.Удм)6